A new central station for a unified city: predicting impact on property prices for urban railway network extensions in Berlin - Gabriel M. Ahlfeldt (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
This paper develops a framework for predicting impact of urban railway network extensions on property prices. Impact of market potential and access to employment is assessed within a hedonic model environment employing potentiality variables and highly disaggregated data. Based on empirical results, expected impact on property prices is assessed for proposed railway extensions connecting Berlin's new central station to the existing metrorail and suburban railway network. Relying on simulated changes in population and employment potentialities, expected increase in aggregated land value is compared for residential and business properties. Application of highly disaggregated data allows detailed mapping of expected pattern of impacts.
Keywords: R12; R23; R42; R52; 330; Urban Transport; Market Access; Employment Access; Land Values; Polycentric City; Berlin